Guanxi and job search in Singapore. - Tsai, Meow Ling. (2009)
The subject of guanxi and its relationship with the job search process has been extensively researched by prominent scholars like Granovetter (1973; 1974), Wegener (1991), Marsden and Hurlbert (1988). However, the results drawn from such studies have largely been based on research conducted in the context of Western societies. The generalisability of these results have been challenged by researchers lil e Bian (1994) in recent studies based on subjects in China which brought into question the effects of demographic, socio-economic, institutional and cultural differences on the relationship between guanxi and the job search process. This prompted the present research which is aimed at studying the extent to which guanxi is relied upon in the job search process and the generalisability of existing literature in the context of Singapore. A questionaire survey was conducted which drew 512 respondents from 9 major industries in Singapore. The results of the survey drew sharp contrasts with some of the existing literature.